The Influence of Human Capital, Structure Capital and Relationship Capital on the Performance of Hospitality Companies in Star Hotels in South Kalimantan - Humaidi Humaidi (Cita Konsultindo Research Center, 2024)
Capital and Relationship Capital on the Performance of Star Hotel Companies in South Kalimantan. The specific objectives of this research are 1. Analyzing the influence of Human Capital on Hospitality Company Performance, 2. Analyzing the influence of Capital Structure on Hospitality Company Performance, and 3. Analyzing the influence of Relationship Capital on Hospitality Company Performance. The research method used is a quantitative approach with an explanatory type. The sample in this study was 57 general managers/hotel owners/who were given mandates by the general manager/hotel owner. Data was collected using a questionnaire, data analysis was carried out using the PLS (Partial Least Square) analysis model using the SmartPLS package computer program. The results of data processing using the PLS (Partial Least Square) analysis model using the help of the SmartPLS computer program, the results show that Human Capital, Structure Capital and Relationship Capital affect the Performance of Hospitality Companies in Star Hotels in South Kalimantan Keywords: Human Capital, Structure Capital, Relationship Capital, Performance of Hospitality Companies